SISTEM INFORMASI MANAJEMEN AKADEMIK DAN KEUANGAN YAYASAN AN-NAWAWI AL-HAKIIMIY MENGGUNAKAN METODE PROTOTYPING - Ekaputra, Galang Prasetya; Afwani, Royana; Ratnasari, Dwi (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2025)
Effective management is a crucial aspect in the operational dynamics of educational institutions. This research aims to develop a Website-Based Academic and Financial Management Information System for the An-Nawawi Al-Hakiimiy Foundation using the prototyping method. The system, developed using the Laravel framework, is designed to optimize various academic and financial management processes, including administration, student and teaching staff data management, attendance tracking, student evaluation and assessment, charity (infaq) recording, and financial management. Through the prototyping method, the system was developed incrementally by involving users in both the design and testing processes. The User Acceptance Testing (UAT) results demonstrated an average assessment score of 95.3%, indicating that the system is highly effective and ready for implementation. This research is expected to significantly enhance the efficiency and effectiveness of the foundation's operational management through the utilization of information technology.